The role of marginal workers in Danish unemployment - Saman Darougheh (Danmarks Nationalbank, 2023)
Unemployment risk is highly heterogeneous in Denmark: a group of marginal workers constitutes 15 per cent of the labour force but makes up roughly 60% of the unemployed in Denmark. These marginal workers cycle more through jobs, have longer and more frequent spells of unemployment and leave their jobs at higher pace. Empirical evidence suggests that marginal workers are less productive than the average worker. They are also more likely to be dependent on labour income: marginal workers have less potential income insurance via partners or parents. These findings better allow us to forecast the development of unemployment, output, and wages.
Keywords: 330; Arbeitslosigkeit; Erwerbsverlauf; Lebensbedingungen; Dänemark